Risk Factors of Ischemic Stroke in Young Adults: A Chinese Single-Center Study - Tang, Mingyu; Han, Guangsong; Yao, Ming; Peng, Bin; Zhu, Yicheng; Zhou, Lixin; Ni, Jun (Frontiers in Neurology, 2022)
Introduction The etiology and risk factor profile of ischemic stroke in young adults are different from those in older patients. However, current etiological classifications are more applicable for the older adults, posing a challenge to the diagnosis of young patients with ischemic stroke. In this study, we applied a modified risk factor categorization previously used in the International Pediatric Stroke Study (IPSS) to describe the risk factor profiles of Chinese young patients with ischemic stroke and explore the sex and age differences in the distribution of risk factors. Methods This is a single-center retrospective study. Patients aged 18–50 years with a first-ever ischemic stroke admitted to the Peking Union Medical College Hospital between 2013 and 2020 were consecutively included. The risk factors of patients were collected and divided into 10 categories according to the modified IPSS criteria and the sex and age differences were explored. Results A total of 538 patients were enrolled in this study. The median age was 39 years and 62.6% were men. At least one IPSS risk factor category was identified in the 93.3% of all patients. The most common IPSS subtype was atherosclerosis-related risk factors (61.7%), followed by prothrombotic states (27.3%), chronic systemic conditions (24.7%), arteriopathy (16.2%), and cardiac disorders (10.4%). Chronic systemic conditions were more prevalent in patients aged <35 years (34.0 vs. 19.6%, p < 0.05) and women (43.3 vs. 13.6%, p < 0.0001). Atherosclerosis-related risk factors were more dominant in patients aged ≥35 years (72.6 vs. 41.9%, p < 0.0001) and men (77.2 vs. 35.8%, p < 0.0001). Conclusions The IPSS classification might be a potential tool to better identify the risk factors of ischemic stroke in young adults.